Kasus Gigitan Ular di Daerah Pertanian Perkebunan Kabupaten Jember: Studi Deskriptif terhadap Korban Gigitan Ular di Dua Rumah Sakit Pemerintah Kabupaten Jember - Rismawan Yunanto; Lantin Sulistyorini (Jurnal Kesehatan dr. Soebandi, 2021)
Introduction: The snakebite cases in Jember as agricultural areas are the potential problem to threaten a person's life. Jember, where most residences are working in the agriculture and plantation sectors, has a very high risk of being bitten by a poisonous snake. Objective: To describe the snakebite cases in the agricultural area from two public hospitals of Jember. Methods: This was a cohort design with a retrospective approach. Two public hospitals in Jember were selected (dr. Soebandi and Kalisat hospital). The medical records were used to explore the data with a total sampling technique. We selected 162 medical records in total (2017-2019) for secondary data resources. The data collection tool used was a checklist sheet based on the guidelines from WHO. Results: Most snakebite victims were male and were farmers with a mean age of 40.95 (SD = 18.97). Most of the victims were bitten in the legs/feet (53,7%). More victims could not identify the snake species (48,8%), but more of them were identified as a green snake (42,6%) and Naja sputatrix (6,2%). They used a constricting method (32,7%) with a rope or cloth to prevent the poison move through the blood vessel. Most victims had mild envenomation (59,9%). Swelling (53,1%), local pain (32,1%), and dizziness (9,4%) were the most common symptoms after the snakebite. The treatment of snakebite victims mostly used 1st dose (83,3%). The nurse also reported several nursing diagnoses such as acute pain (68,5%), risk of infection (22,8%), and skin problem (5,6%). Most of the patients only stay ≤ one day (69%) in the hospital. Conclusion: Snakebites from poisonous snakes are a threat to the agricultural area of Jember. No victims adopted either of the WHO-recommended first aid methods. Most of them had mild envenomation with only a 1st dose treatment.